2018
DOI: 10.1371/journal.pone.0200680
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-based quantitative proteomic analysis of alterations in the intestine of Hu sheep under weaning stress

Abstract: When Lambs are weaned off ewe’s milk, metabolic, structural, and functional changes often occur in the small intestine. Because information on the effects of weaning stress on the proteome of the intestine is limited, an animal model was established with eight pairs of twin lambs divided into artificially reared and ewe-reared groups, which was followed by proteome analysis using iTRAQ technology. Changes occurred in the morphology of the intestine and 5,338 proteins in three biological replicates with less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Similarly, this disease occurs most frequently within the two weeks after weaning and is characterized by a profuse diarrhea, dehydration, significant mortality, and loss of body weight of pigs [27]. Our previous study showed a sudden change in the feeding system due to early weaning resulted in changes of the intestinal morphology and functions [28], that may trigger reductions in digestive and absorptive capacities. Studies suggest that increasing weaning age reduces stress associated with this period and allows animals to have a more mature gastrointestinal tract and become increasingly familiar with solid feed during milk-period with an improvement in growth performance [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, this disease occurs most frequently within the two weeks after weaning and is characterized by a profuse diarrhea, dehydration, significant mortality, and loss of body weight of pigs [27]. Our previous study showed a sudden change in the feeding system due to early weaning resulted in changes of the intestinal morphology and functions [28], that may trigger reductions in digestive and absorptive capacities. Studies suggest that increasing weaning age reduces stress associated with this period and allows animals to have a more mature gastrointestinal tract and become increasingly familiar with solid feed during milk-period with an improvement in growth performance [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…The same animals were used according to our previous study ( 6 ). In summary, eight pairs of twin neonatal ram Hu lambs born on the same day with almost the same body weight (2.75 ± 0.2 kg) were randomly divided into the two groups.…”
Section: Methodsmentioning
confidence: 99%
“…A PPI network was drawn using Cytoscape and the cytoHubba application was used to identify the top 10 hub genes ( 19 , 20 ). The isobaric tags for relative and absolute quantification (iTRAQ) data of the same samples has been published in the previous study ( 6 ). In this integrative study, DEGs were identified by RNA-seq.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In veterinary science, recent investigations using these novel quantitative technologies to detect possible biomarkers of diagnostic and understand the prognosis of diseases in dogs (Martínez-Subiela et al, 2017;Franco-Martínez et al, 2018) have been reported. Also, studies performed in sheep using these techniques to evaluate the alterations in the intestine associated with under weaning stress using jejunum samples (Cui et al, 2018) or to consider age-related changes in the cerebrospinal fluid (Chen et al, 2018) have been published. However, to the best of our knowledge, no reports currently exist on the use of isobaric tagging technology in saliva samples to detect possible biomarkers of stress in sheep.…”
Section: Introductionmentioning
confidence: 99%